(untitled) (International Journal of Environmental Sciences, 2025)
The development and adoption of Virtual Reality (VR) and Extended Reality (XR) technologies are gaining momentum in the aviation sector with promising improvements in various dimensions. The purpose of this study is to assess the applications of VR/XR from the prospective of pilot/crew training, maintenance operations, and passenger use. Information was gathered from a systematic survey of stakeholders in aviation from engineers to pilots to passengers to obtain inputs from multiple strata. Results show that VR/XR is most effective in enhancing the training deliverables and safety procedures, has moderate effect on the supporting maintenance tasks, and enhances the passenger experience with stimulating and interactive environments. Initial doubt of VR/XR solutions’ applicability for aviation Not that long ago, VR/XR was no more than a tool used only in consumer-based sectors of the industry, yet the survey results highlight that at least for Emirates and all other airlines it is a testing ground with great potential for efficiency improvement and passenger services.